THE MECHANISM OF THE BOSE–EINSTEIN CONDENSATION AND ITS ROLE IN THE OCCURRENCE OF THE NORMAL CURRENTS AND SUPERCURRENTS - Kato, Takashi (MATTER: International Journal of Science and Technology, 2015)
The mechanism of the Bose–Einstein condensation and its role in the occurrence of the normal currents and supercurrents is investigated. In particular, the mechanism of the formation of Cooper pairs and their role in the occurrence of non dissipative diamagnetic supercurrents is investigated. In the previous works [1–7], we suggested that in the materials with large HOMO-LUMO gaps, t he Cooper pairs are formed by the large HOMO-LUMO gaps as a consequence of the quantization of the orbitals by nature, and by the attractive Coulomb interactions between two electrons with opposite momentum and spins occupying the same orbitals via the positively charged nuclei. On the other hand, according to the recent experimental research (Wehlitz et. al; 2012), the Cooper pairs have been observed at room temperatures in the neutral benzene (6an), naphthalene (10ac), anthracene (14ac), and coronene molecules. That is, our prediction in our theoretical researches [1–7] can be well confirmed by the recent experimental research (Wehlitz et. al; 2012), and our previous theory can be reasonably applied to the explanation of the mechanism of the occurrence of the granular high temperature superconductivity in carbon materials. Related to seeking for the room-temperature superconductivity, in this article, we compare the normal metallic states with the superconducting states. Furthermore, in this article, we elucidate the mechanism of the Ampère’s law (experimental rule discovered in 1826) in normal metallic and superconducting states, on the basis of the theory suggested in our previous researches.